Presenting the statistical results - Ng, K.H.; Peh, W.C.G. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2009)
Statistical methods are reported in a scientific paper to summarise the data that has been collected for a study and to enable its analysis. These methods should be described with enough detail to allow a knowledgeable reader who has access to the original data to verify the reported results. This article provides basic guidelines to aid authors in reporting the statistical aspects of the results of their studies clearly and accurately.